2019
DOI: 10.1186/s12885-019-5499-2
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced breast cancer treated with neoadjuvant chemotherapy and adjuvant radiotherapy: a retrospective cohort analysis

Abstract: Background Neoadjuvant chemotherapy (NAC) is increasingly used to treat locally advanced breast cancer (LABC). Improved response to NAC correlates with better survival outcomes. The dual purpose of this study is to report recurrence and survival outcomes for LABC patients treated with NAC, surgery and adjuvant radiotherapy and to correlate these outcomes with tumour response after NAC using multiple response assessment methods. Methods All LABC patients treated for cura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
2
23
0
1
Order By: Relevance
“…In order to find more prognostic factors, we found that the hormone receptor status of the patient before surgery and the size of the patient's tumor were related to the survival prognosis of the patient: the smaller the tumor, the longer the OS/DFS (p <0.001, p = 0.004); compared with HR negative, HR positive can obtain longer OS and DFS (p = 0.003, p = 0,011). Jonathan et al's analysis of 103 neoadjuvant chemotherapy studies for locally advanced breast cancer found that the tumor size of patients before chemotherapy was related to LRR (p = 0.003) [30] , and our results are consistent with this. Chou et al confirmed that the younger patients (<50years) is the only independent factor favorable for LRR-freesurvival in patients with breast cancer after NAC with concurrent epirubicin and docetaxel [18] .…”
Section: Discussionsupporting
confidence: 90%
“…In order to find more prognostic factors, we found that the hormone receptor status of the patient before surgery and the size of the patient's tumor were related to the survival prognosis of the patient: the smaller the tumor, the longer the OS/DFS (p <0.001, p = 0.004); compared with HR negative, HR positive can obtain longer OS and DFS (p = 0.003, p = 0,011). Jonathan et al's analysis of 103 neoadjuvant chemotherapy studies for locally advanced breast cancer found that the tumor size of patients before chemotherapy was related to LRR (p = 0.003) [30] , and our results are consistent with this. Chou et al confirmed that the younger patients (<50years) is the only independent factor favorable for LRR-freesurvival in patients with breast cancer after NAC with concurrent epirubicin and docetaxel [18] .…”
Section: Discussionsupporting
confidence: 90%
“…Dynamic contrast-enhanced MRI is the most sensitive of available imaging modalities in characterization of breast malignant tumours as a functional technique that allows the evaluation of residual viable tumour after neoadjuvant therapy by detecting changes in tumour vascularity [7][8][9][10][11][12][13][14]. Multiple studies have clarified that breast MRI is the most accurate imaging modality to determine disease response to neoadjuvant chemotherapy, with sensitivity approaching 90% and specificity of 60% to 100%, and it is particularly helpful in patients with confirmed multifocal and multicentric tumours on the pre-treatment study [1,2,4,7,8,[15][16][17]. Breast MRI has been considered to have a role in guiding breast cancer surgery by differentiating residual tumour from pathological complete response after neoadjuvant therapy, and planning resections to achieve clear margins in BCS [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the incidence of breast cancer has decreased significantly around the world, but the 5-year survival rate of BRCA patients is still 67.6% (26) , and there are still many key issues that have not been resolved. To a certain extent, the decline in mortality is due to advanced medical examination methods (27) , advanced diagnostic techniques (28) , and advanced treatment methods (29) . Among them, targeted therapy has a very good effect in prolonging the survival time of patients, but the most challenging problem in tumor resistance and the burden on the economy.…”
Section: Discussionmentioning
confidence: 99%